Steepest ascent tariff reforms - Pascalis Raimondos-Møller; Alan D. Woodland (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper introduces the concept of a steepest ascent tariff reform for a small open economy. By construction, it is locally optimal in that it yields the highest gain in utility of any feasible tariff reform vector of the same length. Accordingly, it provides a convenient benchmark for the evaluation of the welfare effectiveness of other well known tariff reform rules, as e.g. the proportional and the concertina rules. We develop the properties of this tariff reform, characterize the sources of the potential welfare gains from tariff reform, use it to establish conditions under which some existing reforms are locally optimal, provide geometric illustrations and compare welfare effectiveness of reforms using numerical examples. Moreover, being a general concept, we apply it to the issue of market access and examine its implications. Overall, the paper's contribution lies in presenting a theoretical concept where the focus is upon the size of welfare gains accruing from tariff reforms rather than simply with the direction of welfare effects that has been the concern of the literature.
Keywords: F15; 330; Zolltarif; Außenhandelsliberalisierung; Wohlfahrtseffekt; Kleines-offenes-Land; Wirtschaftsmodell